2018
DOI: 10.9745/ghsp-d-18-00093
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual Bleeding Changes Are NORMAL: Proposed Counseling Tool to Address Common Reasons for Non-Use and Discontinuation of Contraception

Abstract: A new family planning counseling tool uses the simple mnemonic device “NORMAL” to help family planning counselors and providers communicate to their clients key messages about menstrual bleeding changes associated with use of hormonal contraception and the copper IUD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…Health workers, including CHWs, involved in providing family planning education and provision should be equipped to provide reproductive education to help women understand and differentiate between nonharmful and harmful side effects. FHI360 has developed a job aid called "NORMAL" to help health workers counsel clients on expected changes of menstruation on various forms of hormonal contraception [9]. There is evidence that job aids with accurate injectable information have been shown to increase injectable use in low-resource settings and could be adapted to the Ghanaian context [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Health workers, including CHWs, involved in providing family planning education and provision should be equipped to provide reproductive education to help women understand and differentiate between nonharmful and harmful side effects. FHI360 has developed a job aid called "NORMAL" to help health workers counsel clients on expected changes of menstruation on various forms of hormonal contraception [9]. There is evidence that job aids with accurate injectable information have been shown to increase injectable use in low-resource settings and could be adapted to the Ghanaian context [30].…”
Section: Discussionmentioning
confidence: 99%
“…Side effects include menstrual changes (heavier bleeding, amenorrhea or oligomenorrhea), changes in weight, headaches, dizziness, nausea, and cardiovascular impacts. In addition, women may harbor fears of long-term effects of contraceptive use, such as infertility and childbirth complications [8,9]. A 2014 systematic review found a significant proportion of women attributed their unmet need for family planning to a fear of side effects: 28% in Africa, 23% in Asia, and 35% in Latin America and the Caribbean [10].…”
Section: Introductionmentioning
confidence: 99%
“…Data were then compiled in a single dashboard so results could be compared and discussed. The dashboard will be updated on a regular basis as new data become available; the current version is available online through the Knowledge for Health platform 38 . There were some challenges with implementation of this approach across countries and projects.…”
Section: Implementation Of the Global Lng Ius Learning Agendamentioning
confidence: 99%
“…The dashboard will be updated on an ongoing basis. The current version (as of November 2018) is available online in the IUD Toolkit on the Knowledge for Health platform 38 …”
Section: Implementation Of the Global Lng Ius Learning Agendamentioning
confidence: 99%
“…During clinical consultations, providers should address the benefits of menstrual regulation and suppression, highlighting these as safe options for women, to reduce misinformation and knowledge disparities. Additionally, providers globally should discuss the monthly bleeding patterns associated with different contraceptive options to reduce health concerns and contraceptive discontinuation [23, 47]. This may improve the acceptability of contraceptive options, including LARC, that function to reduce menstrual frequency and may open up further options for women.…”
Section: Discussionmentioning
confidence: 99%